THE EFFECTIVENESS OF LEARNING COMMUNITY TECHNIQUE ON ENGLISH ESSAY WRITING SKILLS - Franscy Franscy; Leroy Holman Siahaan (University of Kuningan, 2023)
This research is designed to measure the effectiveness of learning community technique on English Essay Writing skills, based on the result of preliminary observation which showed that students had some problems that related to the result of their writing skill which still have not achieved the expected aims. This research used classroom action research method involving 30 students as sample of the research. For the data collecting technique, this research used quantitative data and qualitative data. Quantitative data was taken from the results of the pre-test and post-test, while qualitative data was taken during the process of observation and action. Then the results of the research showed that the percentage value of student activity in attending lectures had increased, the result of the percentage increase in student activity seen from the percentage of students who were very active and active in cycle 1 was only 36.7%, then increased in cycle 2 to 63.3%. Then the results of learning to write English essays for students also increased, with an average score in cycle 1 of 60.17 and cycle 2 there was an increase in the average score of 9.96 to 70.13. The use of the learning community technique to improve students' English abilities has a favourable effect, particularly on the growth of students' ability to write English essays.